THE IMPLEMENTATION OF PROBLEM BASED LEARNING THROUGH AUDIO VISUAL MEDIA IN IMPROVING STUDENT’S BASIC LEVEL OF CRITICAL THINKING ABILITY AND HISTORY LEARNING OUTCOMES - Irfan Diko Mohammad; Mohamad Na'im; Rully Putri Nirmala Puji (JURNAL HISTORICA, 2019)
The aim of this study are (1) to improve students' ability of critical thinking basic level in historical subject through the implementation of problem based learning using audio visual for students at eleventh class of social SMA 1 ARJASA 2018/2019. (2) to improve the history outcomes through the implementation of problem based d learning using visual audio for students at eleventh class of social SMA 1 ARJASA 2018/2019. This research was classroom action research. Moreover, the subject’s of this research ware the students at eleventh class of social SMA 1 ARJASA which the number of the participants was 35 students. The research design was using Kemmis’s & Taggret’s research model with stages for each cycle. Each cycle consisted of planning, acting, observing, and reflecting. This research consisted of three cycles. Besides, the data collection of this research used observasion, interview, test, and documenter. For the analysis data, this research usedquantitative and qualitative technique. The research result showed that there was any improvement of students’ ability of critical thinking and history outcomes subject. The percentage of students’ critical thinking of the first cycle, it showed as many as 52. 40% clasically. Then, for the next cycle, it improved as many as 66. 23%, and for the last cycle, the percentage was 77. 67%. And for the percentage of students’ outcomes of historical subject was as many as 78. 34%. Then, for the second cycle as 80. 4%, and for the last cycle, the percentage was 81. 71%. It can be concluded that the utilization of problem based learning through visual audio improve’s students’ ability of critical thinking and their output of historical subject.